Facial Feature Localization and Analysis Using Machine Learning - Dinesh Jadhav,; Vishal Gadade,; Dnyaneshwar Bhusare,; Suyash Khatavkar,; R.K Patel, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The facial feature localization system with machine learning (ML) is an innovative solution designed to accurately detect and locate key facial landmarks. By integrating advanced ML algorithms, the system processes images or video streams in real time to identify the positions of facial features such as the eyes, nose, mouth, and jawline. The ML component analyses the data to precisely locate these features, enabling applications in areas like facial expression analysis and biometric verification. This approach enhances accuracy by adapting to various lighting conditions, face orientations, and individual facial variations. The system’s scalability and flexibility further extend its utility, supporting diverse applications across industries like healthcare, security, and human-computer interaction. Overall, this project represents a significant advancement in facial feature localization, using IoT and ML to enable more effective and accurate facial analysis. By adapting to various lighting conditions, face orientations, and individual facial variations" to "by adapting to diverse lighting conditions, different face orientations, and individual facial variations, ensuring reliable performance in various environments.
Keywords: Facial Feature Localization; Real-time Processing; Machine Learning; Key Facial Features; Detection; Application